Exploring the Management of Inclusive Education at Sekolah Kebangsaan Ayer Hitam - Gusti Gusti; Saipul Annur; Yuniar Yuniar (Yayasan Zia Salsabila, 2026)
This study aims to explore and analyze the management of inclusive education at Sekolah Kebangsaan Ayer Hitam, Malaysia. The research focuses on the strategies implemented in the practice of inclusive education, the challenges faced by the school, and the impact of inclusive education management on the academic and social development of students with special needs. A qualitative case study approach was employed, utilizing in-depth interviews, participant observations, and document analysis as data collection techniques. The findings indicate that Sekolah Kebangsaan Ayer Hitam adopts two inclusion models full and partialin accordance with students’ physical and cognitive conditions. Key strategies include differentiated instruction, collaboration between mainstream and special education teachers, continuous teacher training, and support from parents and external communities. Despite supportive government policies, such as the “No-Reject Policy,” limited resources and the shortage of trained educators remain significant challenges in the implementation process. The study concludes that effective inclusive education management requires synergy between policy, teacher competency, family support, and community engagement. These findings are expected to contribute to the development of more effective inclusive education policies and practices in the future.